The Illustrated Mum - Wilson, Jacqueline (Corgi Books, 1999)
She loves Marigold too, but sometimes she just can't help wishing she were more normal . . . This powerful and memorable tale for older readers now includes a special introduction from Jacqueline Wilson.
Keywords: Juvenile literature-Fiction